Interpreting Buridan critical essays - Johnston, Spencer; Lagerlund, Henrik 1970- (Cambridge University Press, 2024)
John Buridan (d. 1362) is one of the great thinkers of the later Middle Ages. He is perhaps best known for his contributions to logic, but the range of his thought is wide. This volume of new essays, written by leading Buridan scholars, places Buridan in his philosophical context and examines his writings on logic, modal logic, paradoxes, metaphysics, epistemology, and natural philosophy. It also introduces several new topics of discussion that have not so far been dealt with in scholarship on Buridan, such as his theory of knowledge, his view of artefacts, his conception of women, his writing on emotions, and his moral philosophy. Together the essays produce a rich picture of Buridan's thought and underline the continuing relevance of his philosophical concerns